1981
DOI: 10.1302/0301-620x.63b4.6457838
|View full text |Cite
|
Sign up to set email alerts
|

Clinical studies of isolated disc resorption in the lumbar spine

Abstract: Low lumbar pain with radiation into the leg is a common symptom pattern caused by a number of pathological processes. Isolated disc resorption is one such entity which can be readily identified and is amenable to surgical treatment. This study consisted of two groups of patients. Group I were 50 patients suffering from isolated disc resorption at L5-S1 with ill-defined low backache extending into the buttocks and down one or both legs, but not into the feet. Clinical signs ofnerve root dysfunction were found i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
6
0
1

Year Published

1982
1982
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 0 publications
1
6
0
1
Order By: Relevance
“…They stressed that the morphology of the ligament was inconstant and in some cases it was found to be compressing the nerve tightly against the ala of the sacrum, corroborating earlier reports by Hadley (1949) and Golub and Silverman (1969). Notwithstanding these detailed studies, analyses of failed attempts at surgical decompression of suspected nerve root entrapment published by Macnab (1977) and by Venner and Crock (1981) have suggested that the anatomical factors underlying entrapment syndromes are still not fully understood.…”
Section: Introductionsupporting
confidence: 55%
“…They stressed that the morphology of the ligament was inconstant and in some cases it was found to be compressing the nerve tightly against the ala of the sacrum, corroborating earlier reports by Hadley (1949) and Golub and Silverman (1969). Notwithstanding these detailed studies, analyses of failed attempts at surgical decompression of suspected nerve root entrapment published by Macnab (1977) and by Venner and Crock (1981) have suggested that the anatomical factors underlying entrapment syndromes are still not fully understood.…”
Section: Introductionsupporting
confidence: 55%
“…Such a process would affect the loading capabilities and segmental motion of the involved segment, thereby contributing not only to disc degeneration of the involved segment, but, because the distribution of stress forces will be altered, the adjacent level may be affected to some degree as well (49)(50)(51)(52)(53)(54).…”
mentioning
confidence: 99%
“…33 Age-related changes in disc mechanics are exaggerated if the disc shows signs of structural disruption such as anular fissures, endplate fracture, and gross height loss. 23 However, links between disc degeneration and segmental instability are not straightforward because some degenerative changes, such as vertebral osteophytes and disc resorption, 34 probably reduce spinal movements rather than increase them. Indeed, instability has been described as a transitional stage in the degenerative process, lying between some initial dysfunction and subsequent restabilization or repair 35,36 so naturally occurring spinal degeneration could be associated with hypermobility or hypomobility, depending on which stage has been reached.…”
mentioning
confidence: 99%